Deconsolidation and Its Interdependent Mechanisms of Fibre Reinforced Polypropylene. Issue 8 (October 2015) - Brzeski, Markus; Mitschang, Peter
Thermoplastic composites offer the possibility of post processing by re-melting of the polymer, but this can lead to a loss of consolidation. The aim of this study is to investigate and quantify the mechanisms leading to deconsolidation. A model is introduced based on the first law of thermodynamics including the following mechanisms: decompaction of the fibre reinforcement network affected by the stored energy during compaction, void evolution due to the surface tension and the gas expansion, moisture in the polymer, and external pressure. These deconsolidation mechanisms are interdependent and have a significant effect on deconsolidation. The modeling approach predicts the deconsolidated state with good agreement to physical measurements.